Attainment of Zero Emission Targets by Transition Towards sustainable development of value of creative products - Wang, Jian; Zhou, Min (Frontiers in Environmental Science, 2023)
Wind, hydropower, solar, and other forms of renewable energy (RE) provide a replacement for conventional sources of energy when the global green and low-carbon transition is considered in broad terms. The possibility of RE is enormous and has just risen to the top of the global energy pyramid. Empirical research on China is based on data from 1990 to 2020. An interactive fixed effects panel threshold model is then created to examine the impact of RE production on GHG emissions. We observe that the negative impact of renewable energy development (RED) on carbon dioxide suggests that the substitution function of RE has grown more significant so that it may efficiently ensure the accomplishment of carbon reduction. According to these findings, which are in line with the optimization method, it seems that RED is doing an outstanding job of reaching carbon neutrality. To put it another way, CO2 tends to have a negative impact on RED, which shows that environmental protection is a predictor of RED. The decrease in energy emissions has become a global issue. Because of this, RED is anticipated to bring about the necessary acceleration in light of the recent reversal of fortune. While it is expected that zero-emission competition in the future will reshape the demographics of the globe.